Podróż do źródeł muzyki? Afrykańsko-niemieckie związki muzyczne w I poł. XX wieku - Odoj, Wojciech (Res Facta Nova, 2021)
The article is a review of Anna Maria Busse Berger’s book The Search for Medieval Music in Africa and Germany, 1891–1961: Scholars, Singers, Missionaries. This volume discusses the role of youth movements (Jugendbewegung, Wandervogel, Singbewegung) responsible for creating the cultural life of Germany, and the interdependencies between musicologist-medievalists, ethnomusicologists and missionaries. It also deals with the fascinating, difficult beginnings of comparative musicology, including the story of musicology as a scholarly discipline that was slowly finding its place among other branches of learning that had already been long established at universities.